Design concepts and analysis of a semi-active steering system for a passenger car - Baharom, M; Hussain, K; Day, A J (IMechE, 2009)
The fundamentals and preliminary analyses of an innovative future technology referred to as ‘semi-active steering’ (SAS) are presented in this article. The proposed steering system configuration is similar to a conventional electrical power-assisted steering with the replacement of the rigid steering shaft with a low stiffness resilient shaft (LSRS), the presence of which allows ‘active control’ to be performed on vehicles similar to the concept of full steerby-wire (SBW). But, unlike SBW, the LSRS is an integral part of the system characteristics. The advantages of the semi-active system in comparison with SBW and other conventional systems are demonstrated. A mathematical model to predict the mechanical properties of the LSRS has been developed, and experiments were conducted on a medium-sized car fitted with an LSRS to verify that vehicle stability and drivability can be ensured in the event of active system failure. The results have indicated that the vehicle was stable and safe to be driven at low speeds, and is predicted to be driveable and safe at higher speeds. It is concluded that an SAS system of this type has the potential to improve the safety of SBW systems.